The Connection between Business Ethics and the Company’s Efficiency: A Comparison Analysis of Global Companies - Florina (MIHAI) LETA (Communications of International Proceedings, 2023)
The study is aiming to put into question the largest global companies in their pursuit to development, by analyzing the commitment they are adhering to each day through the ethical code, and how they manage eventual crisis that may appear due to not following the said moral guidelines. The literature is focused on putting into question the problem of business ethics; however, it has not been centered on how the largest companies are acting on this topic. The article’s methodology is through observing and analyzing their ethical code, whether they are more successful due to this aspect and identifying any similarities between them, as major players on the global economy. The findings will be mutually beneficial both for the academic world, as it will open more discussion topics to be further looked into and for the business environment, due to the fact that will prove the benefits that following an ethical code will bring to the company as opposed to not having one. Through the article the hopes are to be beneficial to the research community, as it can be further development in other approached subjects and to slowly bring more information and conclusions to the topic of ethical business.
Keywords: Business; Efficiency; Ethic Code